Tenancy exempt from registration under the Malaysian torrens system / Mazelan Jamaludin - Jamaludin, Mazelan (Faculty of Law, 1982)
The Law governing land tenure and dealings in West Malaysia is based solely on the torrens system, which was adopted from the Australia Torrens System but with very substantial modificatians. Where it does not directly importing the English equitable concepts. In Australia, there exists a du y system of land law namely the common Law system of Lana tenure imported directly from England as well as the torrens system devised in Australia.